Review: Regulation of Phytohormones and Environmental Stresses to Increase the Production of Plant Secondary Metabolites - Selis Meriem (University of Brawijaya, 2021)
Secondary metabolites are synthesized by plants when subjected to abiotic and biotic stresses as a defense mechanism and play an ecologically vital role both as pollination attractants and as repellents. These compounds are not essential for the process of growth and development but provide a significant impact on human welfare in various aspects as pharmaceuticals and therapeutics, aroma and taste, biopesticides, and agrochemicals. This natural product has high economic and commercial value, so it is important to explore it along with the increasing needs of consumers and industry at a large scale. Various extensive studies were carried out to improve and increase the production and accumulation of secondary metabolites. One of the strategies adopted in this review is the role of exogenous phytohormones in triggering the production of important secondary metabolites based on their classification, namely terpenoids, phenols, and flavonoids, as well as alkaloids and nitrogen-containing compounds. Bioregulators work as elicitors to induce the production of secondary metabolites through up-regulation of specific gene expression. In some cases, the application of phytohormones combined with exposure to extreme abiotic stresses showed overexpression of secondary metabolite synthesis compared to treatment with only those subjected to phytohormone. The abiotic stress of irradiation, UV-B, temperature, drought, ultrasonic, salinity, and metal stress was discussed in this study. Oxidative conditions under environmental changes trigger the plant to produce reactive oxygen species (ROS), which induce various secondary metabolites as part of the regulation of antioxidant systems. Micropropagation of medicinal plants by the addition of exogenous growth regulators could enhance the production and accumulation of important secondary metabolites.